Social workers' perceptions of barriers to interpersonal therapy implementation for treating postpartum depression in a primary care setting in Israel. (20th July 2017) - Bina, Rena; Barak, Adi; Posmontier, Barbara; Glasser, Saralee; Cinamon, Tali
Abstract: Research on evidence‐based practice (EBP) implementation in social work often neglects to include evaluation of application barriers. This qualitative study examined social workers' perspectives of provider‐ and organisational‐related barriers to implementing a brief eight‐session interpersonal therapy (IPT) intervention, a time‐limited EBP that addresses reducing depressive symptoms and improving interpersonal functioning. Implementation took place in a primary care setting in Israel and was aimed at treating women who have postpartum depression (PPD) symptoms. Using purposeful sampling, 25 primary care licensed social workers were interviewed between IPT training and implementation regarding their perceived barriers to implementing IPT in practice. Data analysis was facilitated using a phenomenological approach, which entails identifying the shared themes and shared experiences of research participants regarding barriers to implementing IPT. Three themes emerged from the analysis of interviews: Perceived lack of flexibility of IPT intervention in comparison with more familiar methods social workers previously applied, specifically regarding the number of sessions and therapeutic topics included in the IPT protocol; insecurity and hesitance to gain experience with a new method of intervention; and organisational barriers, including difficulties with referrals, the perception of HMOs as health facilities not suitable for therapy, and time constraints. Addressing perceived barriers of social workers toward implementing EBPs, such as IPT for postpartum depression, during the training phase is crucial for enabling appropriate implementation. Future training should include examining practitioners' attitudes toward implementation of EBPs, as part of standardised training protocols.